Use Of Natural Dyes From Plants In Coloring Woven Yarns - Rahmadina, Nazwa; Ramadani, Rizka Aulia; Samsul Hadi (JFARM - Jurnal Farmasi, 2024)
The use of natural dyes as an environmentally friendly alternative to reduce the use of synthetic dyes which have a negative impact on the environment. Natural dyes can be obtained from various natural sources such as plants, animal waste, and minerals, with plants being the most common source. Plant pigments such as anthocyanins, tannins, flavonoids, and chlorophyll provide a variety of colors that can be used for coloring. The natural dyeing process involves four stages: making the dye solution, fabric preparation, dyeing, and fixation. Testing the quality of natural dyes includes color visualization tests, color aging, color differences and fastness to washing. The methodology for writing this article is a literature study, reviewing various related research from 2013 to 2023. The results show that several plants such as Tarum, Coconut, Secang, Noni, Turmeric, and Shallots can produce colors such as dark blue, brownish cream, red , yellow, and brownish orange on fabric. In conclusion, natural dyes not only support environmental sustainability but also offer a safe and low-cost coloring alternative, although there are challenges in the manufacturing and application process of these natural dyes.